2012
DOI: 10.1007/s10265-012-0534-2
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of two major clades and early diverged groups within the subfamily Cyperoideae (Cyperaceae) including Korean sedges

Abstract: We aim to present phylogenetic major groups within the subfamily Cyperoideae (Cyperaceae) on the basis of three molecular data sets; nuclear ribosomal internal transcribed spacer and 5.8S ribosomal RNA region, the ribulose-1, 5-bisphosphate carboxylase/oxygenase large subunit gene, and trnL intron and trnL-F intergenic spacer. Three molecular data and two combined data sets were used to obtain robust and detailed phylogenetic trees by using maximum parsimony and Bayesian inference, respectively. We analyzed 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(87 citation statements)
references
References 39 publications
10
69
0
8
Order By: Relevance
“…Continued work towards inclusion of more informative molecular regions or increasing 550 taxonomic sampling has resulted in good support for seven major lineages within a clade consisting of tribes Cariceae, Dulichieae and Scirpeae (CDS), but relationships between these major lineages and the identity of Cariceae's sister group has remained elusive (Léveillé-Bourret et al 2014). Previous studies have placed Cariceae sister to a monophyletic Scirpeae (Muasya et al 2009) or nested within a paraphyletic Scirpeae and sister to either a Trichophorum Clade 555 (Léveillé-Bourret et al 2014), the genus Calliscirpus (Gilmour et al 2013) or a clade consisting 29/52 of the Scirpus Clade + Zameioscirpus Clade (Jung and Choi 2012). The only consistency has been the poor support for all backbone relationships, a consequence of a rapid radiation (ca.…”
Section: Phylogenetic and Taxonomic Implicationsmentioning
confidence: 99%
“…Continued work towards inclusion of more informative molecular regions or increasing 550 taxonomic sampling has resulted in good support for seven major lineages within a clade consisting of tribes Cariceae, Dulichieae and Scirpeae (CDS), but relationships between these major lineages and the identity of Cariceae's sister group has remained elusive (Léveillé-Bourret et al 2014). Previous studies have placed Cariceae sister to a monophyletic Scirpeae (Muasya et al 2009) or nested within a paraphyletic Scirpeae and sister to either a Trichophorum Clade 555 (Léveillé-Bourret et al 2014), the genus Calliscirpus (Gilmour et al 2013) or a clade consisting 29/52 of the Scirpus Clade + Zameioscirpus Clade (Jung and Choi 2012). The only consistency has been the poor support for all backbone relationships, a consequence of a rapid radiation (ca.…”
Section: Phylogenetic and Taxonomic Implicationsmentioning
confidence: 99%
“…However, selected Scleria species have been included in the sampling of larger Cyperaceae phylogenies. Most of these studies show Scleria to be the sister taxon of tribe Bisboeckelereae (Muasya & al., 1998;Hirahara & al., 2007;Hinchliff & al., 2010;Jung & Choi, 2013;Viljoen & al., 2013), while other studies point towards Sclerieae nested in a paraphyletic Bisboeckelereae (Muasya & al., 2009;Hinchliff & Roalson, 2013). In Hinchliff & Roalson (2013), 12 species of Scleria were included, but no morphologically recognisable groupings were retrieved.…”
Section: Nees 1842mentioning
confidence: 99%
“…remains unsatisfactory because it is defined by the same plesiomorphic characters that have been used since the earliest of classifications, and its status as a natural tribe has been questioned for decades (Goetghebeur, , ; Bruhl, ). Molecular phylogenetic analyses have since shown that Scirpeae forms a strongly supported clade with Cariceae, Dulichieae, the recently discovered Sumatroscirpeae, and the enigmatic monospecific genus Khaosokia D.A.Simpson & al., a lineage comprising ~2250 species, or approximately 41% of all Cyperaceae (Simpson & al., ; Muasya & al., ; Jung & Choi, ; Léveillé‐Bourret & al., ) (Figs. ).…”
Section: Introductionmentioning
confidence: 99%